A selective fluorescent sensor for Cu(II) ion in ethanol and acetone based on BODIPY - Dong, Fengchao; Zhang, Zhenyu; He, Yongwu; Ming, Zhu; Li, Pengfei; Bian, Li (European Journal of Chemistry, 2018)
A selective fluorescent sensor for Cu(II) ion in ethanol and acetone based on boradiazaindacene (BODIPY) has been studied. The selectivity towards Cu(II) ion is good over Ag(I), Cd(II), Fe(III), Hg(II), Ni(II), Pb(II), and Zn(II) ions, only Fe(III), Hg(II) and Ni(II) ions showed a slight interference. The solution showed strong fluorescence intensity after addition of triethanolamine, indicating that the Sensor 1-Cu(II) complex could be reversed by triethanolamine.